Beneficiary-centric decision support framework for enhanced resource coordination in humanitarian logistics: A case study from ASEAN. (November 2022) - Timperio, Giuseppe; Kundu, Tanmoy; Klumpp, Matthias; de Souza, Robert; Loh, Xiu Hui; Goh, Kelvin
Highlights: A multi-method decision support framework to address resource coordination in humanitarian logistics is designed. Planning and execution of supply networks are simultaneously considered. A real-world application in ASEAN is conducted to demonstrate the practical relevance. Data analytics, visualization, and simulation are designed to address the case at hand. Findings of this study suggests beneficiary-centric policies for humanitarian operations management. Abstract: The growing frequency, impact, and complexity of natural- and human-made- disasters have resulted in an increased attention toward humanitarian logistics management practices. With most disasters having a global scale due to the high level of interconnectedness between supply chains, the adequate provision of humanitarian assistance through streamlined logistics systems has become paramount. Correspondingly, the traditional organization- and execution-centric approaches are no longer sufficient, and greater attention to beneficiary- and ecosystem-centric supply chain networks with equal emphasis on planning and execution are necessary. Accordingly, this work proposes a multi-method decision support framework to analyze, visualize, optimize, and simulate supply networks to address the key challenge of resource coordination in disaster response operations. A real-world application to the Disaster Emergency Logistics System for ASEAN (DELSA), the network of pre-positioned stockpiles managed by the ASEAN Humanitarian Agency in ASEAN, is also presented. Results of the analyses show that with the introduction of inventory management policies with safety stock, the DELSA network improves its performance in service level by +41%. Unlike the current practice where inventory decisions are, in most cases, supply-and funds-driven, the findings of this work bring about a paradigm shift for beneficiary-centric policies. More importantly, the analyses of this study could generate practical insights for proper humanitarian logistics planning not only in ASEAN but throughout the world.